RANCANG BANGUN SISTEM PAKAR PENENTUAN PROGRAM STUDI UNTUK CALON MAHASISWA BARU MENGGUNAKAN METODE FORWARD CHAINING - insan tri; Serlianti Waruwu; Agus Budiyantara (Jurnal Komputer dan Teknologi, 2026)
The selection of study programs at ISTEK Widuri often becomes a challenge due to the absence of a structured decision support system. This research develops an expert system based on the forward chaining method to provide study program recommendations based on user input. The development stages include requirements analysis, rule formulation, interface design, implementation using PHP and MySQL, and testing using the black-box method. The system is capable of recommending four study programs: Communication Studies, Social Welfare, Informatics Engineering, and Information Systems. The testing results show that the system runs well and is able to provide appropriate recommendations. Therefore, this system can serve as an effective alternative in assisting prospective students in choosing their study program.